Orthodontic smile: a new categorization of the perfect smile - Dias, Maria do Rosário (2020)
This is an open access article, distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as appropriate credit is given and the new creations are licensed under the identical terms.